Backend Berbasis Laravel dengan Pendekatan Gamifikasi pada Sistem Pelaporan Tugas Harian Mahasiswa - Nasrin Akhsani; Novi Tristanti (TIN: Terapan Informatika Nusantara, 2026)
Management of digital reporting of students' daily assignments still faces various obstacles, such as data inconsistencies, weak activity validation, delays in collecting assignments, and not yet optimal mechanisms that can improve student discipline on an ongoing basis. These problems show the importance of implementing a backend that is structured and capable of effectively supporting the automation of academic processes. This research aims to implement a web-based daily task reporting system backend using the Laravel framework with a gamification approach in the Nugas system. The research uses a qualitative approach with an implementation case study type and an adaptive Waterfall system development method. The research subjects consisted of 10 active students of the Informatics Study Program at Muhammadiyah Karanganyar University who were selected using a purposive sampling technique. Data collection was carried out through semi-structured interviews, observations, questionnaires and system documentation, while data analysis used source triangulation techniques to maintain the credibility of the research results. Backend implementation produces a system with 17 database Tabels, 15 controllers, and 2 main services, namely GamificationService and NotificationService. The results of black box testing on 74 RESTful API endpoints show that 72 endpoints (97.3%) function according to system requirements. Performance testing using Laravel Debugbar on 10 main endpoints shows an average database query time of ~35 ms without any N+1 query problems found, and the cache implementation runs well. Trials on 10 students showed that all respondents successfully submitted assignments and obtained the Early Bird badge, while the average questionnaire score reached 4.16 on a scale of 5 in the good category. This research provides a contribution in the form of a gamification-based Laravel backend implementation model that is integrated with a RESTful API to support the management of academic tasks in a more structured, automatic and scalable manner. Overall, the research results show that the application of gamification elements in the form of points, badges, leaderboards and achievements can increase student motivation in completing academic assignments.